Antibody for detecting p53 protein by immunohistochemistry in normal tissues. Issue 7 (July 1994) - Pezzella, F; Micklem, K; Turley, H; Pulford, K; Jones, M; Kocialkowski, S; Delia, D; Aiello, A; Bicknell, R; Smith, K
Abstract : AIMS--To establish whether PAb248 recognises human p53 as well as murine p53 and if so, to determine its distribution in normal tissues. METHODS--The ability of PAb248 to recognise human p53 was established by analysis of the human osteosarcoma derived Saos-2 cell line, which lacks the p53 gene, before and after transfection with p53 cDNA, using western blotting and immunoprecipitation. Immunostaining on normal tissues and cell lines was carried out using an immunoperoxidase technique. The two anti-p53 antibodies PAb 240 and DO-7 were used as controls. RESULTS--The anti-p53 PAb248 monoclonal antibody stained the Saos-2 cell line after, but not before, transfection with p53 cDNA. Both western blots and immunoprecipitations performed with this antibody revealed a 53, 000 molecular weight band. With immunostaining, this antibody detects p53 protein in most lymphoid and human epithelial cells in a cytoplasmic-perinuclear localisation that has not been described before. In the same tissues nuclear staining could be seen in a few scattered cells using the PAb240 antibody. The topographical distribution of wild type p53 was not related to proliferating areas but, rather, to short-lived populations of cells. CONCLUSIONS--Immunostaining of wild type p53 is demonstrable not only in its nuclear form using antibody PAb240 but also in it common cytoplasmic-perinuclear localisation in normal tissues using the PAb248 monoclonal antibody. This opens up new possibilities for its study in both physiological and pathological conditions.